Civil Liability Insurance Under French Legislation - Biletska, Yuliia (Actual problems of law (Aktual'ni problemi pravoznavstva), 2025)
Civil liability insurance in France is an important institution for the legal protection of victims, as it ensures compensation for damage regardless of the financial status of the perpetrator. However, the main issue remains ensuring effective protection of the victims' rights while maintaining a balance of interests between all parties, including preventing abuse by individuals who seek to avoid personal liability. Important challenges also include insufficient insurance coverage and exemptions from liability.Overall, the analysis of civil liability insurance in France helps to identify both the strengths and problematic aspects of this institution, which is important for improving Ukraine's national legislation.The issue of the legal structure of insurance has been the subject of numerous studies by foreign scholars, but research in this field remains relevant due to its complexity and the need to improve legal regulation.The aim of this study is to analyze the legal regulation of civil liability insurance in France.This article explores the legal regulation of civil liability insurance in France. It examines the main provisions of the French Civil Code and the French Insurance Code that govern the conclusion and execution of civil liability insurance contracts, as well as the conditions for the emergence of insurance obligations.The differentiation of civil liability insurance types based on the criteria of mandatory nature, subject of insurance, field of activity, and liability subject is also explored. The article reviews the key provisions of French legislation regarding the regulation of various types of insurance, such as mandatory and voluntary insurance. Special attention is given to professional liability insurance and motor vehicle owners’ liability insurance.Particular focus is given to the analysis of the «activation of responsibility» principle through the victim’s claim, which is an important element of the legal structure of liability insurance under French law. The risks of insurance abuse by perpetrators are analyzed, as well as the issue of ensuring sufficient insurance coverage. France’s experience in regulating civil liability insurance may be useful for improving Ukraine’s national legislation, which would strengthen the guarantees of victims’ rights and increase the effectiveness of damage compensation mechanisms.